Book Review: Connected intelligence: Transforming education and energy with big data, cloud connectors, and artificial intelligence - Prasart Nuangchalerm (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Annapareddy (2025), the author explains the transformative impact of emerging digital technologies on contemporary society, particularly in the fields of education and energy management. The book presents the concept of connected intelligence in which refers to the integration of artificial intelligence, big data, cloud computing, and interconnected digital infrastructures to support intelligent decision-makingand sustainable education development. The book presents the growing role of artificial intelligence and big data in education. The educational institutions are increasingly adopting data-driven approaches to improve teaching, learning, and administrative processes in all sectors. AI-powered learning systems can provide personalized learning by adapting contemporary contents, learning assessments, and learning pathways to individual needs. Furthermore, the cloud technologies enable scalable and flexible learning environments, supporting online education, collaborative learning, and real-time access to educational resources.